As-needed low-dose inhaled corticosteroid/formoterol therapy in patients with severe asthma included in the German Asthma Net cohort - Hinze, Christopher Alexander; Ehmann, Rainer; Jandl, Margret; Milger-Kneidinger, Katrin; Schmidt, Olaf; Schulz, Christian; Skowasch, Dirk; Welte, Tobias; Buhl, Roland; Hamelmann, Eckard; Idzko, Marco; Taube, Christian; et al. (ERJ Open Research, 2024)
Tweetable abstract ERSpublications - click to tweetAfter the GINA update in 2019, the proportion of SMART therapy increased with evidence for better disease control in SMART patients compared to SABA alone https://bit.ly/3SSPX1C